Efektivitas Ekstrak Beberapa Tumbuhan untuk Pengendalian Keong Mas (Pomacea canaliculata Lamarck) pada Tanaman Padi Sawah: english - Rusli, Rusdi; Martinius, Martinius; Marzuki, Dedi (Plant Protection Department, Faculty of Agriculture, Universitas Andalas, 2019)
Golden snail is an important pest on rice plants in Indonesia. The study purposed to obtain the most effective plant extracts to suppress the golden snail population. The study was conducted at the greenhouse of Faculty of Agriculture, Universitas Andalas, Padang from November to December 2018, using a Completely Randomized Design (CRD) with six treatments and four replications. The treatment was leaf extracts from several plants with a concentration of 10 g/l, that were god’s crown or mahkota dewa (Phaleria macrocarpa), noni or mengkudu (Morinda citrifolia), breadfruit or sukun (Artocarpus altilis), ti plant or andong (Cordyline fruticosa), mangkokan (Nothopanax scutellarium), and control. The parameters observed were mortality of golden snails, percentage of clumps attacked, and intensity of golden snail attacks. The results showed that there were three leaf extracts could suppress golden snail population significantly, ie. Mangkokan, andong and mahkota dewa. The mangkokan leaf extracts was most effective in controlling golden snails which caused mortality of golden snails to reach 100% within 24 hours of exposure so that they did not attack the clumps as a whole.